Exploration of Fatalism and Religiosity by Gender and Varying Levels of Engagement Among Mexican-American Adults of a Type 2 Diabetes Management Program - Cindy Lynn Salazar-Collier (Frontiers in Public Health, 2021)
Objectives: Purpose of study is to explore the roles religiosity and fatalistic beliefs play in diabetes management among newly, currently, and long-term enrolled Mexican-American participants in a Type 2 diabetes mellitus (T2DM) chronic care management program.Methods: In 2017, study participants (n = 15) completed a semi-structured interview in their preferred language (English or Spanish). Sample was stratified by amount of time individual had been enrolled as a participant of the Salud y Vida program: newly, currently, or long-term. Interviews assessed religious beliefs, beliefs concerning the cause(s) of diabetes, perceived relationship between religiosity and fatalistic beliefs with T2DM management, and the appropriateness of discussing such topics with a health professional. Interview responses were analyzed using ATLAS.ti 8.Results: Themes identified included: perceived autonomy over diabetes prognosis, motivators for self-care, discussions of personal beliefs in the healthcare setting, and the church's role in diabetes management.Conclusions: Among this sample, religiosity and religious fatalism played a complex role in coping with and managing diabetes. Long-term enrolled and male participants expressed beliefs of divine control over health, and a connection between religiosity and health behavior. Long-term enrolled participants felt religious and fatalistic beliefs may be suitable and beneficial to discuss in the healthcare setting.